Transnational capitalist class - Vuletić, Vladimir (Sociološki pregled, 2023)
The text analyses the question why theories with the concept of a transnational class in its centre are insufficiently recognized in sociological textbooks. It is an opportunity to present the works of two most important theoreticians with this concept in the centre of their respective theories.